High percentage of undiagnosed HIV cases within a hyperendemic South African community: a population-based study - Vandormael, Alain; Bärnighausen, Till (Journal of epidemiology and community health, 2018)
Background Undiagnosed HIV infections could undermine efforts to reverse the global AIDS epidemic by 2030. In this study, we estimated the percentage of HIV-positive persons who remain undiagnosed within a hyperendemic South African community. Methods: The data come from a population-based surveillance system located in the Umkhanyakude district of the northern KwaZulu-Natal province, South Africa. We annually tested 38 661 adults for HIV between 2005 and 2016. Using the HIV-positive test results of 12 039 (31%) participants, we then back-calculated the incidence of infection and derived the number of undiagnosed cases from this result. Results: The percentage of undiagnosed HIV cases decreased from 29.3% in 2005 to 15.8% in 2011. During this period, however, approximately 50% of the participants refused to test for HIV, which lengthened the average time from infection to diagnosis. Consequently, the percentage of undiagnosed HIV cases reversed direction and steadily increased from 16.1% to 18.9% over the 2012-2016 period. Conclusions: Results from this hyperendemic South African setting show that the HIV testing rate is low, with long infection times, and an unsatisfactorily high percentage of undiagnosed cases. A high level of repeat HIV testing is needed to minimise the time from infection to diagnosis if the global AIDS epidemic is to be reversed within the next two decades.
Published online first 24 November 2017
Gesehen am 27.09.2018